O efeito anti-inflamatório e antioxidante dos polissacarídeos isolados de subprodutos agroindustriais do processamento da acerola (Malpighia emarginata) no modelo de gastropatia induzida por naproxeno em camundongos - Castro, Zulmira de Oliveira (2017)
The peptic ulcer (PU) affects millions of people worldwide, considered heterogenous and multifactorial, is one of the main diseases that affects the gastric mucosa and that has grown the number of cases causing representativeness in the global economy. The acerola (Malpighia emarginata D.C.) is a reddish fruit, originating in the region of the Antilles, north of South America and Central America. Its cultivation had higher growth in the decade of 90 when its high content of vitamin C was discovered. Studies show that the polysaccharide fractions extracted from the byproducts presented pectic nature in association with proteins, being evidenced mainly for those extracted from acerola, pineapple and cashew, effective antioxidant action, suggesting its possible application as natural antioxidants. The present study evaluated the anti-inflammatory and antioxidant activity of polysaccharides from the agro-industrial by-products of the processing of acerola (Malpighia emarginata) in the model of gastric lesion induced by naproxen in mice. Swiss mice were pretreated with saline and / or polysaccharides from acerola processing byproducts (PCA) [3], [10] and [30] mg / kg, by gavage. After 30 minutes, they received naproxen (300 mg / kg, by gavage) or carboxymethylcellulose (0.5% vCMC), and the animals were euthanized 6 hours after the experimental protocol. Stomach segments were collected for analysis of the following parameters: macroscopy, microscopy, GSH, MDA, MPO, TNF-α, IL-6 and IL-1 immunohistochemistry. PCA at doses of [3], [10] and [30] mg / kg by gavage significantly reduced macroscopic and microscopic gastric lesion induced by naproxen. PCA at doses of 10 and 30 mg / kg prevented depletion at GSH concentrations, reduced MDA concentrations and reduced neutrophil infiltration. PCA at the dose of 30 mg / kg reduced the concentrations of proinflammatory cytokines TNF-α and IL-6. In the immunohistochemical analysis for IL-1 (interleukin) the pretreated group with PCA 30 mg / kg achieved a significant reduction in IL-1 expression when compared to the NPX group. IL-10 expression was elevated in the pre-treated group with 30 mg / kg PCA when compared to the NPX group. For the determinations of TNF-α and COX-2 the pretreated group with PCA 30 mg / kg obtained a reduction in expression when compared to the group treated with NPX. From the data obtained in this work, it can be concluded that PCA has an anti-inflammatory and antioxidant effect in the experimental model of gastric ulcer induced by naproxen.